2016
DOI: 10.1007/s40279-016-0601-2
|View full text |Cite
|
Sign up to set email alerts
|

How to Prevent Injuries in Alpine Ski Racing: What Do We Know and Where Do We Go from Here?

Abstract: Alpine ski racing is known to be a sport with a high risk of injury and a high proportion of time-loss injuries. In recent years, substantial research efforts with regard to injury epidemiology, injury etiology, potential prevention measures, and measures’ evaluation have been undertaken. Therefore, the aims of this review of the literature were (i) to provide a comprehensive overview of what is known about the aforementioned four steps of injury prevention research in the context of alpine ski racing; and (ii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
131
4
8

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(159 citation statements)
references
References 81 publications
13
131
4
8
Order By: Relevance
“…The present study was the first prospective study on injury incidence and severity involving youth alpine ski racers younger than 15 years, as suggested by Spörri et al1 Relatively low incidence of traumatic and overuse injuries and comparably high prevalence of illnesses were revealed. No sex-specific differences were present, except for females presenting a higher chance of having no medical problems.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The present study was the first prospective study on injury incidence and severity involving youth alpine ski racers younger than 15 years, as suggested by Spörri et al1 Relatively low incidence of traumatic and overuse injuries and comparably high prevalence of illnesses were revealed. No sex-specific differences were present, except for females presenting a higher chance of having no medical problems.…”
Section: Discussionsupporting
confidence: 55%
“…The most commonly injured body part is the knee; rupture of the anterior cruciate ligament (ACL) is the most frequent traumatic injury 5,6. However, reliable collection of injury data in youth alpine ski racers remains a challenge; therefore, studies involving youth ski racers, particularly with regard to overuse injuries, are less common and represent a gap in scientific research on injury prevention in alpine ski racing 1. Additionally, off-season and off-snow training should be investigated 1.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, substantial research efforts concerning injury causes and prevention measures have been undertaken (Spörri et al, 2016b). However, most alpine ski racing-related research has focused on traumatic injuries, while overuse injuries have received little attention (Supej et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Since a combination of these factors is known to be related to high spinal disc loading (Nachemson, 1981; Wilke et al, 1999; Haid and Fischler, 2013), and has been suggested to be attributable to different types of spine deteriorations (Rachbauer et al, 2001; Hangai et al, 2009), they may be considered important mechanisms leading to overuse injuries of the back in alpine ski racing (Spörri et al, 2015a,b, 2016a). …”
Section: Introductionmentioning
confidence: 99%
“…Recently, a nonsystematic narrative review was conducted on the general topic of injury prevention in elite alpine ski racing 22. Given the paucity of studies contributing higher level evidence on ACL injury in alpine ski racing, and a larger emphasis on qualitative research studies, a nonsystematic narrative review was deemed the most appropriate methodology for the present review.…”
Section: Methodsologymentioning
confidence: 99%